Survey and Design of Individual Housing Projects: Situation and Solutions for Ha Tinh Province, Vietnam - Nguyen, S. M.; Tran, V. B.; Nguyen, D. D. (Engineering, Technology & Applied Science Research, 2022)
Survey and design processes are considered essential stages and directly affect the quality and cost of construction works. This study aimed to investigate the existing limitations in the survey and design stages of individual housing projects in Ha Tinh province, Vietnam, and to propose specific solutions to improve them. These solutions can contribute to eliminating unexpected problems or errors during the construction process of individual housing projects in Vietnam.